Enhancing vascularization of a gelatin-based micro-cavitary hydrogel by increasing the density of the micro-cavities. (7th October 2016) - Fu, Jiayin; Fan, Changjiang; Lai, Wei Shan; Wang, Dongan
Abstract: The transport of nutrients and oxygen by vascular networks into engineered tissue constructs is critical to their successful integration into host tissues. Hydrogel has achieved some promising results as scaffolds for vascularization. However, the vascularization of hydrogel is still constrained by its inherent submicron- or nano-sized pores. In this study, two gelatin-based micro-cavitary gel (Gel-MCG) constructs with varying densities of micro-cavities were developed with a photocrosslinkable gelatin methacrylate (Gel-MA) precursor and porogenic gelatin microspheres (MS), and their functions in supporting vascularization within hydrogels were evaluated with endothelial progenitor outgrowth cells (EPOCs). The increase of cavitary density could enhance the vascularization of Gel-MCG constructs. After 14 d of culture in vitro, the vascularization of Gel-MCG constructs with higher cavitary density was significantly superior to that of gelatin spongy control and the fusion of vascularized cavities in the constructs could be observed. Further subcutaneous implantation of the Gel-MCG constructs with higher cavitary density into nude mice also showed obvious vascular invasion from host tissues. Taken together, these results indicate that the increase in cavitary density can efficiently facilitate the vascularization of Gel-MCG constructs both in vitro and in vivo and that such highly-porous Gel-MCG constructs have great potential to be a promising scaffold for the development of vascularized tissue constructs.